The association between coronaphobia and attitude towards COVID-19 Vaccine: A sample in the east of Turkey - Turan, G. B.; Aksoy, M.; Ozer, Z.; Demir, C. (Masson Editeur, 2022)
Purpose. - This study was conducted to examine the association between coronaphobia and attitude towards COVID-19 vaccine in the society. Methods. - This cross-sectional descriptive study was conducted with snowball sampling method between December 30, 2020 and January 10, 2021. The survey form was sent online to individuals who were 18 years of age and older. 1252 individuals who responded to the surveys were included in the study. The data were collected by using Descriptive Information Form, Attitudes towards the Covid-19 vaccine scale and Coronavirus 19 Phobia Scale (CP19-S). Descriptive statistics and Pearson Correlation analysis were used in the evaluation of data. Results. - In the study, it was found that the participants had a mean ATV-COVID-19 scale positive attitude sub-dimension score of 2.81 +/- 1.04, while they had a mean negative attitude sub-dimension score of 2.95 +/- 0.78 and a mean total score of 2.89 +/- 0.78. It was found that the participants had a mean C19P-S psychological sub-dimension score of 21.03 +/- 5.36, a mean psychosomatic sub-dimension score of 10.30 +/- 4.11, a mean social sub-dimension score of 15.04 +/- 4.71, a mean economic sub-dimension score of 8.89 +/- 3.46 and a mean total scale score of 55.28 +/- 15.00. It was found in the study that there was a positive association between the participants' C19P-S and social sub-dimension and ATV-COVID-19 and positive attitude sub-dimension, while there was a negative association between ATV-COVID-19 and negative attitude sub-dimension (p < 0.05). Conclusions. - It was found that the participants had a moderate level of coronavirus phobia and positive attitudes towards the vaccine. It was found that positive attitudes towards COVID-19 vaccine increased as the coronavirus phobia increased. (C) 2021 L'Encephale, Paris.
Keywords: Attitudes towards vaccination; Coronavirus 19 Phobia; COVID-19